Bidirectional catalyst design for lithium–sulfur batteries: phase regulation cooperates with N-doping. Issue 44 (31st October 2022) - Liang, Xinqi; Cai, Jinyan; Qiu, Saisai; Niu, Shuwen; Liu, Yulong; Wang, Xi; Wang, Gongming; Chen, Zhen; Chen, Minghua
Abstract : N-doping and phase regulation of MoS2 via room temperature NH3 plasma technology achieve efficient bidirectional catalysis for lithium–sulfur electrochemistry. Abstract : Accelerating the reaction kinetics of S species is considered the key to further improving the performance of lithium–sulfur (Li–S) batteries. However, current research on efficient catalysts for S species is mainly limited to unidirectional catalysis, yet both the oxidation and reduction processes of Li–S electrochemistry are integrated and inseparable. Therefore, developing a suitable bidirectional catalyst is critical for practical applications. Herein, we adopted N-doped ultra-thin MoS2 nanosheets anchored on multi-walled carbon nanotubes (N-MoS2 @CNTs) as efficient bidirectional catalysts for fast S species conversion by a fast and highly active NH3 plasma technology under moderate conditions. Reasonable N doping can improve the adsorption ability of soluble lithium polysulfides and effectively inhibit the harmful shuttle effect. In addition, the mild NH3 plasma N-doping strategy can also regulate the favorable phase transition (2H → 1T phase) of the catalyst and further improve the catalytic activity. Benefiting from the N-doping strategy coupled with phase regulation, N-MoS2 @CNTs reduce the nucleation and decomposition barrier of Li2 S, which greatly improves the conversion reaction kinetics of Li–S batteries. The assembled batteries comprising a S/N-MoS2 @CNT composite cathode exhibit a high capacity of 1313.6 mA h g −1 at 0.1C and deliver excellent cycle stability at 1C for 1000 cycles with an ultra-low capacity decay rate of 0.037% per cycle. More importantly, it can be stably cycled for more than 100 cycles even when increasing the sulfur loading to 5.1 mg cm −2 .